The Influence of Bank Employees' Daily Aerobic Exercise Routine on their Emotional Intelligence - E. , Chandramouli; C., Kathiravan; S., Velmurgan (International Journal of Psychosocial Rehabilitation, 2022)
The banking sector contributes significantly to a country's economic growth. The 1991 government policy of economic liberalization resulted in structural reforms in the Indian economy, with banks undergoing several operational modifications. Banks offer a wide range of services to their customers, and technological advancements have given the banking industry a whole new look. Aerobic exercise is defined as any physical activity that causes you to sweat, breathe harder, and makes your heart beat quicker than it would at rest. It strengthens the heart and lungs, as well as the cardiovascular system, to better manage and supply oxygen throughout the body. "Emotional Intelligence" is defined as "the ability to identify, use, understand, and control emotions in good ways to reduce stress, communicate effectively, empathize with others, overcome problems, and defuse conflict." This study aims to find out the relationship and impact of Regular Aerobic Exercise practice on Emotional Intelligence among the bank employees in Cuddalore district. For that purpose, the independent variables are Aerobic exercise, and the dependent variables are Emotional Intelligence and its sub-variables: Self-Awareness, Managing Emotions, Self-Motivation, Recognizing the Emotions of Others, and Handling Relationships. This study is descriptive in nature, and the data will be collected using a questionnaire from 150 bank employees in Cuddalore district who regularly practice aerobic exercise. ANOVA analysis will be employed to conduct the analysis in this study. From the findings of this research, we concluded there is a positive relationship and significant influence of Regular Aerobic Exercise practice on the Emotional Intelligence of Bank Employees in Cuddalore district.